2015
DOI: 10.17221/8420-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the dexmedetomidine, midazolam, butorphanol, and atropine combination on plasma oxidative status and cardiorespiratory parameters in raccoon dogs (Nyctereutes procyonoides)

Abstract: ABSTRACT:Oxidative stress in the body occurs when the production of free radicals overwhelms the antioxidant defence systems. This study aimed to investigate the effects of a combination of dexmedetomidine, midazolam, butorphanol, and atropine (DMBA) as an anaesthetic on plasma oxidative status in twelve raccoon dogs. Baseline measures were recorded prior to anaesthesia, and then the animals were anaesthetised with the combination of dexmedetomidine (25 µg/kg), midazolam (0.45 mg/kg), butorphanol (0.25 mg/kg),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…MDA serum level was significantly reduced by DEX in human patients undergoing pulmonary aortic surgery when used at infusion dose in general anesthesia [ 52 ]. Increased SOD and CAT activity was also observed following DEX in raccoon dogs when compared with baseline [ 53 ]. Similar results were found by the use of intravenous DEX infusion combined with ISO inhalation that reduced the oxidative stress and hypoxic pulmonary vasoconstriction in one-lung ventilated patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…MDA serum level was significantly reduced by DEX in human patients undergoing pulmonary aortic surgery when used at infusion dose in general anesthesia [ 52 ]. Increased SOD and CAT activity was also observed following DEX in raccoon dogs when compared with baseline [ 53 ]. Similar results were found by the use of intravenous DEX infusion combined with ISO inhalation that reduced the oxidative stress and hypoxic pulmonary vasoconstriction in one-lung ventilated patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the application of an effective anesthetic method is especially important. The use of an appropriate dose of anesthetic in the operation can relieve the pain of the patient, and is also able to reduce the damage to the patient tissue ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increased activity of superoxide dismutase dismutases the superoxides and resulted in H 2 O 2 generation, which is decomposed by catalase into H 2 O and O 2 . Feng et al (2015) found an increase in superoxide dismutase, glutathione peroxidase and catalase level during anaesthesia due to the activation of antioxidant mechanism to prevent the oxidative stress. The results of the present study was supported by the findings of Bisla et al (2004), Serin et al (2008) and Sankar et al (2010).…”
Section: Antioxidantsmentioning
confidence: 96%